Comparison of HPV testing and cervical cytology in prevention of cervical cancer - Klaudia Remjasz; Katarzyna Kosz; Aleksandra Kuchnicka; Julia Kuchnicka; Jakub Aleksandrowicz; Martyna Zielińska; Natalia Zarankiewicz; Wojciech Siedlecki; Klaudia Sapuła (Kazimierz Wielki University, 2022)
Introduction and purpose  This article aims to compare two guiding methods of cervical cancer screening: cervical cytology   and HPV testing. The objective is to provide information on which method   is currently more relevant in the early detection of precancerous lesions and and therefore should   be more frequently used.        Materials and method  This review was mainly based on articles from around the world collected in Pubmed in 2003-2022, medical books and websites. The research was done by looking through keywords as follows: "cervical cancer", "cytology", "HPV testing".  Results  All selected studies have demonstrated that HPV testing is a more appropriate indicator for initial  high-grade CIN (cervical intraepithelial neoplasia) than cytology.  Conclusions  According to the cited researches, the public health system should definitely pay more attention   to HPV testing as the first stage of cervical cancer screening. Moreover,   it should clarify by comparing all advantages and disadvantages of methods, which further diagnostic pathway is the most effective and has the best outcomes for the patients.   Keywords  cervical cancer, cervical screening, cytology, HPV primary screening, HPV testing